Statistical optimisation of phenol degradation and pathway identification through whole genome sequencing of the cold-adapted antarctic bacterium, Rhodococcus sp. strain AQ5-07 - Lee, Gillian Li Yin; Zakaria, Nur Nadhirah; Convey, Peter; Convey, Hiroyuki Futamata; Zulkharnain, Azham; Suzuki, Kenshi; Abdul Khalil, Khalilah; Shaharuddin, Noor Azmi; Alias, Siti Aisyah; Gerardo, González-Rocha; Ahmad, Siti Aqlima (MDPI, 2020)
Study of the potential of Antarctic microorganisms for use in bioremediation is of increasing interest due to their adaptations to harsh environmental conditions and their metabolic potential in removing a wide variety of organic pollutants at low temperature. In this study, the psychrotolerant bacterium Rhodococcus sp. strain AQ5-07, originally isolated from soil from King George Island (South Shetland Islands, maritime Antarctic), was found to be capable of utilizing phenol as sole carbon and energy source. The bacterium achieved 92.91% degradation of 0.5 g/L phenol under conditions predicted by response surface methodology (RSM) within 84 h at 14.8 °C, pH 7.05, and 0.41 g/L ammonium sulphate. The assembled draft genome sequence (6.75 Mbp) of strain AQ5-07 was obtained through whole genome sequencing (WGS) using the Illumina Hiseq platform. The genome analysis identified a complete gene cluster containing catA, catB, catC, catR, pheR, pheA2, and pheA1. The genome harbours the complete enzyme systems required for phenol and catechol degradation while suggesting phenol degradation occurs via the β-ketoadipate pathway. Enzymatic assay using cell-free crude extract revealed catechol 1,2-dioxygenase activity while no catechol 2,3-dioxygenase activity was detected, supporting this suggestion. The genomic sequence data provide information on gene candidates responsible for phenol and catechol degradation by indigenous Antarctic bacteria and contribute to knowledge of microbial aromatic metabolism and genetic biodiversity in Antarctica.